Detecting trends in tree growth: not so simple - Bowman, David M.J.S; Brienen, Roel J.W; Gloor, Emanuel; Phillips, Oliver L; Prior, Lynda D (Trends in plant science, 2013)
Tree biomass influences biogeochemical cycles, climate, and biodiversity across local to global scales. Understanding the environmental control of tree biomass demands consideration of the drivers of individual tree growth over their lifespan. This can be achieved by studies of tree growth in permanent sample plots (prospective studies) and tree ring analyses (retrospective studies). However, identification of growth trends and attribution of their drivers demands statistical control of the axiomatic co-variation of tree size and age, and avoiding sampling biases at the stand, forest, and regional scales. Tracking and predicting the effects of environmental change on tree biomass requires well-designed studies that address the issues that we have reviewed.